Various electroanalytical methods for the determination of uranium in different matrices - Alankar Shrivastava; Jitendra Sharma; Vishal Soni (Faculty of Pharmacy, Cairo University, 2013)
Uranium is a toxic material hence numerous body systems such as the kidney, brain, liver, and heart can be affected by uranium exposure. The main effect is kidney toxicity. Uranium is a naturally occurring element found in low levels in all rock, soil, and water. All uranium isotopes may also cause radiation hazards, thus without any doubt an analysis of such materials in the surrounding environment is very important. The presented review is a summarization of all electroanalytical techniques for the determination of uranium and its compounds in various matrices. Totally 43 different methods are found in our literature survey. Out of these three are polarographic, 25 potentiometry, five capillary electrophoresis and 28 voltametric methods are available in the literature. Interferences of different ions and applications in different matrices are also given for each method.